2017
DOI: 10.21859/johe.4.3.63
|View full text |Cite
|
Sign up to set email alerts
|

Introducing a combined pattern to empower risk assessment knowledge of safety, health and environment in health care systems

Abstract: Background and Objective: Knowledge management is the optimal use of knowledge to achieve intended purposes. Given the type of activity of health care systems and their high health and safety risks, knowledge of health and safety executive (HSE) principles not only contributes to patient safety and health, but also enhances the health and safety of employees through raising awareness and using others' experiences. Materials and Methods: In this study, a questionnaire with 11 key questions was developed. Then, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The current study presented the model in three dimensions: (a) deployment of related technologies (modern antecedents), b) deployment of management systems (core components), and c) improvement of management culture (HSE). In addition, 14 domains were obtained, including 1-hardware and software improvement, 1396) on introducing a combined pattern to empower risk assessment knowledge of safety, health and environment in health care systems showed that although knowledge management is an emerging process in Iran, new patterns should be implemented in all dimensions and activities in this field (19).…”
Section: Resultsmentioning
confidence: 99%
“…The current study presented the model in three dimensions: (a) deployment of related technologies (modern antecedents), b) deployment of management systems (core components), and c) improvement of management culture (HSE). In addition, 14 domains were obtained, including 1-hardware and software improvement, 1396) on introducing a combined pattern to empower risk assessment knowledge of safety, health and environment in health care systems showed that although knowledge management is an emerging process in Iran, new patterns should be implemented in all dimensions and activities in this field (19).…”
Section: Resultsmentioning
confidence: 99%